Implementasi Kepemimpinan Transformasional di Sekolah Dasar Negeri 07 Simpuruik - Mayang Azwardi; Hidral Azhari; Asmendri; Milya Sari (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research aims to explain the Implementation of Transformational Leadership at State Elementary School 07 Simpuruik. This research uses qualitative methods with data collection techniques through observation and interviews which involve collecting information and data from various sources found in related educational institutions, the results of research carried out in the field are added. with relevant sources, articles, related notes and also includes journals related to the topic you want to complete. Leadership in educational institutions is one of the determinants of educational success and the achievement of educational goals in these institutions. Transformational leadership plays a very important role in the process of improving teacher performance, where this is proven by a leader who has a high transformational attitude, this leader will provide a positive example to employees. Especially in the implementation of e-performance management, teachers and school principals are required to be able and understand the flow of performance management well.